Like Blood in Water : Five Mininovels - Tarnavsʹkyĭ, I︠U︡riĭ (Book collections on Project MUSE., 2007)
A surrealist account of the creative and descriptive arts. In these five surrealist collages, waking life continually gives way before the onslaught of dreams. Yuriy Tarnawsky has condensed the vastness of scope typical of novels into shorter fragments-mininovels-that require the reader's active participation. The tone is a balance of dead-pan comedy and solemn gothic, sometimes a near-parody of wide-eyed candor, sometimes recounting utterly mad or barely conceivable states of affairs. A candidate for major surgery struggles unsuccessfully to avoid it. Two strang.